2009
DOI: 10.1016/j.neuroscience.2008.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of activation of group III metabotropic glutamate receptors on spinal synaptic transmission in a rat model of neuropathic pain

Abstract: Chronic neuropathic pain remains an unmet clinical problem because it is often resistant to conventional analgesics. Metabotropic glutamate receptors (mGluRs) are involved in nociceptive processing at the spinal level, but their functions in neuropathic pain are not fully known. In this study, we investigated the role of group III mGluRs in the control of spinal excitatory and inhibitory synaptic transmission in a rat model of neuropathic pain induced by L5/L6 spinal nerve ligation. Whole-cell recording of lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 47 publications
(70 reference statements)
2
41
0
Order By: Relevance
“…Group II mGluRs are present in the dorsal root ganglion and spinal superficial dorsal horn (Jia et al, 1999;Carlton et al, 2001), and stimulation of these mGluRs in the spinal cord generally depresses synaptic transmission (Gerber et al, 2000;Zhou et al, 2007). We have demonstrated that activation of group I and group III mGluRs has distinct effects on synaptic transmission in the spinal dorsal horn in neuropathic pain Zhang et al, 2009;Li et al, 2010). In contrast, the nerve injury-induced changes in group II mGluR function in the spinal dorsal horn and their functional significance in neuropathic pain is still not clear.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…Group II mGluRs are present in the dorsal root ganglion and spinal superficial dorsal horn (Jia et al, 1999;Carlton et al, 2001), and stimulation of these mGluRs in the spinal cord generally depresses synaptic transmission (Gerber et al, 2000;Zhou et al, 2007). We have demonstrated that activation of group I and group III mGluRs has distinct effects on synaptic transmission in the spinal dorsal horn in neuropathic pain Zhang et al, 2009;Li et al, 2010). In contrast, the nerve injury-induced changes in group II mGluR function in the spinal dorsal horn and their functional significance in neuropathic pain is still not clear.…”
Section: Introductionmentioning
confidence: 81%
“…Recordings of postsynaptic currents were performed by using the whole-cell voltage-clamp method, as described previously (Zhou et al, 2008a(Zhou et al, , 2009Zhang et al, 2009). Each slice was placed in a glass-bottomed chamber and continuously perfused with Krebs' solution at 5.0 ml/min at 34°C maintained by an inline solution heater and a temperature controller.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Glutamate-mediated synaptic input and NMDAR activity of lamina II neurons are increased in spinal cords of SNL rats (32,33). We determined whether increased NMDAR activity contributes to synaptic disinhibition and the shift in E glycine of lamina II neurons caused by nerve injury.…”
Section: Nerve Injury Switches Glycine-mediated Synaptic Inhibition Tmentioning
confidence: 99%